The ESA Active Dosimeter (EAD) system onboard the International Space Station (ISS) - Ulrich Straube; Thomas Berger; Matthias Dieckmann (Zeitschrift für Medizinische Physik, 2024)
Ionizing radiation in general and mixed fields of space radiation in particular pose a risk of serious harm to human health. The risk of such adverse effects increases with the duration of the mission, and for all missions outside the protective properties of the Earth’s magnetic field and atmosphere. Accordingly, radiation protection is of central importance for all human spaceflight, which is recognized by all international space agencies. To date various systems, analyze and determine the exposure to ionizing radiation within the environment and to the crew onboard the International Space Station (ISS). In addition to this operational monitoring, experiments and technology demonstrations are carried out. This to further enhance systems capabilities, to prepare for exploratory missions, to the Deep Space Gateway and/or to enable for human presence at other celestial bodies. Subsequently the European Space Agency (ESA) decided early to support the development of an active personal dosimeter. Under the auspices of the European Space Research and Technology Center (ESTEC) together with the European Astronaut Center's (EAC) Medical Operations and Space Medicine (HRE-OM) team, a European industrial consortium was formed to develop, build, and test this system. To complete the ESA Active Dosimeter (EAD) Technology Demonstration in space, EAD components were delivered to ISS with the ESA’s space missions ‘iriss’ and ‘proxima’ in 2015 and 2016. This marked Phase 1 (2015) and 2 (2016–2017) of the EAD Technology Demonstration to which focus is given in this publication. All EAD systems and their functionalities, the different radiation detector, their properties, and calibrations procedures are described. Emphasis is first on the “iriss” mission of September 2015, that provided a complete set of data for an entire space mission from launch to landing, for the first time. Data obtained during Phase 2 in 2016–2017 are discussed thereafter. Measurements with the active radiation detectors of the EAD system provided data of the absorbed dose, dose equivalent, quality factor as well as the various dose contributions during the crossings of the South Atlantic Anomaly (SAA) and/or resulting from galactic cosmic radiation (GCR). Results of the in-flight cross-calibrations among the internal sensors of the EAD systems are discussed and alternative usage of the EAD Mobile Units as area monitors at various different locations inside the ISS is described.